Mental Rotation Test Performance in Brazilian and German Adolescents: The Role of Sex, Processing Speed, and Physical Activity in Two Different Cultures - Jansen, Petra; Paes, Flávia; Hoja, Sabine; Machado, Sergio (Frontiers in Psychology, 2019)
It was the main goal of this study to investigate performance on the mental rotation test (MRT) performance in Brazilian and German adolescents. Mental rotation is the ability to mentally transform a three-dimensional stimulus in mind and relates to science education. 60 German and 60 Brazilian adolescents (76 males and 44 females, 11-17 years) completed a mental rotation test, a physical activity and media use questionnaire and a cognitive processing speed test. The result showed no difference between Brazilian and German adolescents in the cognitive processing speed measurement. German adolescents are more active and show a less media use compared to the Brazilian adolescents. Furthermore, German adolescents demonstrate a better MRT performance than Brazilian ones, as well as boys show a better performance than girls do. A multiple regression analysis indicated that the MRT performance could be predicted by nationality, sex and cognitive processing speed. Since cognitive processing speed did not differ between Brazilian and German adolescents, the worse MRT performance of the Brazilian adolescents could be explained by different educational systems. Further studies have to follow which investigate the reasons for the different nations in more detail.